Cultura organizacional y su relación con la corrupción (2019)
The following article constitutes the accomplishment of a bibliographical revision looking to identify the existent relation of the organizational culture and its elements with the phenomenon of corruption within the organizations and to try to look for some possible alternative of solution to this issue. With the review carried out, it is found that the organizational culture does indeed have an influence on the materialization of an act of corruption when it does not meet the expectations of the people or when they do not find a shared meaning, which can generate phenomena such as those denominated by several authors as counterproductive work behavior or uncivil behavior which could derivate in a corrupt behavior. The incidence of culture is not the only or fundamental thing for a person to choose a behavior of this type, but it can help to generate conditions for it to occur; Ultimately, the decision to carry out a corrupt behavior falls exclusively on each person, which leads us to the field of personality, psychology and psychoanalysis